Pelatihan Penyusunan Modul Ajar Berdiferensiasi Berbasis Digital Dalam Upaya Implementasi Kurikulum Merdeka Dalam Komunitas Belajar Sekolah Dasar - Rafli, Muhammad Febri; Mahlianurrahman, Mahlianurrahman; Sari, Cut Kumala; Syarah, May (Journal Of Human And Education (JAHE), 2024)
This activity is carried out on the implementation of an merdeka curriculum based on the needs and characteristics of students. Teachers are required to be able to design learning tools that differentiate all aspects of students by utilizing digital technology. The purpose of this activity is to increase the knowledge and skills of elementary school teachers in compiling diagnostic assessments and compiling digital-based differentiated teaching modules. The implementation of this activity was carried out at SD Negeri 2 Tualang Cut, Manyak Payed District, Aceh Tamiang Regency involving 23 participants. This activity was carried out using two methods, namely providing seminars on diagnostic assessment and differentiated learning concepts and training in developing digital-based differentiated teaching modules. The results of the activity showed a positive impact in improving the ability of teachers to compile learning documents. This activity has achieved the success indicator, namely the teacher has a good understanding of the material presented by getting a score of 91.13. In addition, teachers have also been able to compile digital-based differentiated teaching modules by getting an average score of 91.67. This proves that there is an increase in teacher knowledge about diagnostic assessment and differentiated learning and teacher skills in preparing digital-based differentiated teaching modules in elementary schools. One of the implications of this activity is that teachers can implement differentiated learning in accordance with the learning documents that have been prepared.